A CASE STUDY OF SUCCESSFUL TREATMENT OF HYDROALLANTOIS IN A MURRAH BUFFALO - Selvaraju, M.; Manokaran, S (International Journal of Allied Sciences (IJAS), 2023)
Hydroallantois is a gestational disorder that affects cattle and buffalo during the last phase of the third trimester. The condition is characterized by a sudden increase in allantoic fluid, resulting in the bilateral enlargement of the abdomen. This paper presents a case study of a 10-year-old Murrah buffalo with sudden bilateral abdominal enlargement within the last 20 days. The animal was successfully managed using a combination of different drugs for the induction of parturition and supportive fluid therapy to avoid hypovolemic shock due to the sudden expulsion of allantoic fluid. The importance of early diagnosis, correct decision fluid therapy, and proper management with strategic medication to avoid hypovolemic shock and save the life of the animal is highlighted.